Pengaruh Kemudahan, Keamanan Dan Kepercayaan Bertransaksi Terhadap Minat Menggunakan QRIS (Quick Response Indonesian Standard) Pada Pelaku UMKM Di Kabupaten Boalemo - Riflan Buluati; Deby R. Karundeng; Moh. Afan Suyanto (Wahana, 2023)
The purpose of this study was to analyze the influence of the variables of convenience, security and trust in transactions that affect the interest in using QRIS (Quick Response Indonesian Standard) for MSME actors in Boalemo Regency. The data used in this study is primary data sourced from filling out questionnaires. The research population is 78 respondents using the incidental method. The analytical technique used to answer research problems and test hypotheses is multiple regression analysis. The findings of this study are (1) ease of transaction has a positive and significant effect on the intention to use QRIS, (2) transaction security has a positive and significant effect on the intention to use QRIS, (3) transaction confidence has a positive and significant effect on the intention to use QRIS